Internationalization in European Higher Education: New Data from the Frontlines - Rumbley, Laura; Hoekstra-Selten, Jody (International Higher Education, 2024)
New research from the European Association for International Education—the EAIE Barometer, third edition (2024)—captures perspectives on the state of internationalization across the European Higher Education Area from the viewpoint of frontline professionals working in this field. Drawing on more than 2800 responses from 46 EHEA countries, insights are provided into matters of job satisfaction, institutional approaches and performance, and the perceived influence of national and European-level actors on internationalization.